Impact of clinical pharmacy recommendations and patient counselling program among patients with diabetes and cancer in outpatient oncology setting - SANCAR, MESUT (WILEY, 2020)
Introduction The simultaneous occurrence of diabetes and cancer may complicate the management of both conditions resulting in poor prognosis and more deterioration of patient-related outcomes. Objective To assess the effective provision of clinical pharmacy services and pharmacist-led counselling program on improving patient-related outcomes among patients with diabetes and newly diagnosed with cancer during chemotherapy administration. Methods A single-centre, prospective, randomised, controlled study was carried out on patients with diabetes newly diagnosed with cancer during chemotherapy administration at the outpatient oncology setting. Patients were assigned as a normal care group receiving only normal care by the oncology care providers and an intervention group receiving both normal and clinical pharmacy care through an extensive oral and written patient education, pharmacotherapy optimisation and regular recommendations for diabetic self-care activities with three-month follow-up. Results Patients within the intervention group showed a better glycaemic control (p = .049), a significant increase in medication adherence (p = .0049), a significant increase in diabetes self-care activities, including diet (p = .037), self-monitoring of blood glucose (p = .027) and foot care (p = .0085) and reported a lower deterioration in quality of life. Conclusion Patients with diabetes and cancer receiving chemotherapy experienced improved patient-related outcomes after clinical pharmacy intervention and counselling program compared to the normal care group.
Keywords: cancer; clinical pharmacist; diabetes mellitus; glycaemic Control; patient counselling program; patient-related outcomes; GLYCEMIC CONTROL; CARE; MEDICATION; EDUCATION; VALIDITY; INTERVENTIONS; RELIABILITY; MANAGEMENT; MORTALITY; MELLITUS